2020
DOI: 10.1159/000508303
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, but Not Metabolic Diseases, Is Associated with Risk of Psoriasis: A Population-Based Cohort Study in Taiwan

Abstract: Background: Obesity and metabolic diseases including diabetes, hyperlipidemia, and hypertension are reportedly associated with an increased risk of psoriasis. However, few prospective studies have investigated the association of obesity and metabolic diseases with the risk of psoriasis. Objective: To examine whether obesity or metabolic diseases increase the risk of psoriasis. Methods: Participants were collected from 4 rounds (2001, 2005, 2009, and 2013) of the Taiwan National Health Interview Survey. Inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Before the data were released to the researchers, the identification numbers of the participants were encrypted to protect individual privacy. The NHIRD data have been used widely for research 18‐26 . The diagnostic codes used were based on the International Classification of Diseases, 9th Revision, Clinical Modification (ICD‐9‐CM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the data were released to the researchers, the identification numbers of the participants were encrypted to protect individual privacy. The NHIRD data have been used widely for research 18‐26 . The diagnostic codes used were based on the International Classification of Diseases, 9th Revision, Clinical Modification (ICD‐9‐CM).…”
Section: Methodsmentioning
confidence: 99%
“…The NHIRD data have been used widely for research. [18][19][20][21][22][23][24][25][26] The diagnostic codes used were based on the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM).…”
Section: Data Sourcementioning
confidence: 99%
“…It has long remained unclear whether obesity is a risk factor for the development of psoriasis or its consequence. However, regardless of cause and effect, it has been found that there is an association between obesity and the development and progression of psoriasis (increased BMI is associated with a higher degree of psoriasis severity) (2,(20)(21)(22). Given the fact that the prevalence of psoriasis is increasing while the genetic basis has remained the same, it is believed that environmental factors, including lifestyle and dietary habits, which are modifiable risk factors in the pathogenesis of psoriasis, play an important role in this growing prevalence (2,22).…”
Section: Metabolic Comorbidities Of Psoriasismentioning
confidence: 99%
“…In the presence of the aforementioned comorbidities, dermatologists may help improve the quality of life of patients with psoriasis through early identification of associated comorbidities, implementation of preventive measures, recommendation of appropriate therapies and close follow-up. In patients with high BMI (overweight or obese) the dermatologist may recommend a healthier lifestyle and weight loss, which would improve both the PASI and the patients' quality of life (7,9,20,46). If standard measures are not effective, surgery, such as gastric bypass, may be considered, as it has been reported to reduce the risk of developing psoriasis and improve the prognosis in patients who already have psoriasis (9,(46)(47)(48).…”
Section: Management Of Metabolic Comorbidities In Psoriasismentioning
confidence: 99%
“…Psoriasis is a chronic, immune-mediated skin disease that affects approximately 2–4% of the global population and poses a lifelong burden that influences patients’ quality of life [1, 2]. The interplay of genetic, immunological, and environmental factors has been implicated in the pathogenesis of psoriasis [3].…”
Section: Introductionmentioning
confidence: 99%